Employment Stability: The Private Sector of the Canadian Economy - MacPherson, R. B. (Relations industrielles / Industrial Relations, 1956)
SummaryIn this article, the author gives a special attention to the problem of employment stability in the private sector of the Canadian economy. Before elaborating this theme, he considers the importance of a growth industry and the problems associated with it; he then suggests some solutions and draws some personal conclusions.